A MULTIMODAL LINGUISTIC ANALYSIS OF CHA EUNWOO’S FAREWELL SPEECH: DISCOURSE, PRAGMATIC, AND RHETORICAL STRATEGIES - Eka Hidayati; Deny Hadi Siswanto (CV. Denasya Smart Publisher, 2025)
This study presents a comprehensive linguistic analysis of Cha Eunwoo’s farewell speech in Master in the House (Episode 177), employing an integrated framework of discourse analysis, pragmatics, and rhetorical strategies, complemented by a multimodal approach. The research utilizes a descriptive qualitative methodology, focusing on a single case study of a televised speech. Data were meticulously transcribed from the original video, and a detailed analysis was conducted to investigate how Cha Eunwoo discursively constructs his identity and relationships, navigates social nuances through pragmatic choices in Korean politeness and honorifics, and employs rhetorical appeals, particularly pathos, to foster and maintain audience engagement and parasocial bonds. Furthermore, the analysis examines the interplay of verbal and non-verbal cues, including vocalics, kinesics, and visual context, in shaping the overall communicative impact of the televised speech. Findings reveal a sophisticated balance between personal emotion and public performance, demonstrating how linguistic and multimodal strategies are strategically deployed to reinforce celebrity persona, solidify interpersonal connections within a variety show setting, and ensure sustained fan loyalty within the dynamic landscape of Hallyu. This study contributes to a nuanced understanding of celebrity communication, the evolving dynamics of the Korean Wave, and the complex application of Korean linguistic features in mediated entertainment contexts